2011
DOI: 10.1073/pnas.1110852108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution and steady-state analysis of the fatty acid synthase from Escherichia coli

Abstract: Microbial fatty acid derivatives are emerging as promising alternatives to fossil fuel derived transportation fuels. Among bacterial fatty acid synthases (FAS), the Escherichia coli FAS is perhaps the most well studied, but little is known about its steady-state kinetic behavior. Here we describe the reconstitution of E. coli FAS using purified protein components and report detailed kinetic analysis of this reconstituted system. When all ketosynthases are present at 1 μM, the maximum rate of free fatty acid sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
210
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(222 citation statements)
references
References 29 publications
(47 reference statements)
8
210
2
2
Order By: Relevance
“…repress fatty acid production at higher concentrations (Yu et al, 2011). In addition, the pentadecaheptaene production of recombinant E. coli strain is strongly dependent on the ratio of two key enzymes, SgcE10 and SgcE.…”
mentioning
confidence: 97%
“…repress fatty acid production at higher concentrations (Yu et al, 2011). In addition, the pentadecaheptaene production of recombinant E. coli strain is strongly dependent on the ratio of two key enzymes, SgcE10 and SgcE.…”
mentioning
confidence: 97%
“…Furthermore, during membrane synthesis, ∼20 million molecules of fatty acids are synthesized in Escherichia coli (8). Yu et al (17) reconstituted an in vitro steady-state kinetic system of fatty acid biosynthesis using purified enzymes and observed that the maximum fatty acid production rate obtainable was 100 μM/min. This production rate falls far below the amount of fatty acids required by a cell in vivo [if one assumes a cell volume of 6.7 × 10 −16 L (18) and a generation time of 30 min (19)].…”
mentioning
confidence: 99%
“…Improvements in protein expression and access to stable enzymes have made more complex systems possible, however 1,[9][10][11][12] . In vitro biotransformation systems have been reported in recent years involving systems of over 30 enzymes 13,14 .…”
mentioning
confidence: 99%